2001
DOI: 10.1046/j.1462-5822.2001.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome ploidy in different stages of the Giardia lamblia life cycle

Abstract: The early diverging eukaryotic parasite Giardia lamblia is unusual in that it contains two apparently identical nuclei in the vegetative trophozoite stage. We have determined the nuclear and cellular genome ploidy of G. lamblia cells during all stages of the life cycle. During vegetative growth, the nuclei cycle between a diploid (2N) and tetraploid (4N) genome content and the cell, consequently, cycles between 4N and 8N. Stationary phase trophozoites arrest in the G2 phase with a ploidy of 8N (two nuclei, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
184
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 31 publications
(41 reference statements)
3
184
0
2
Order By: Relevance
“…By mining the Giardia genome database for cyclin homologs (Reiner et al, 2008), several genes have been identified as candidates for a mitotic cyclin on the basis of sequence similarity. Each cell contains two diploid nuclei that are replicated concurrently (Bernander et al, 2001;Sagolla et al, 2006), and then simultaneously segregated to opposite poles of the cell by two separate spindles, prior to cytokinesis (Nohýnkova et al, 2000;Sagolla et al, 2006). Thus, the cell cycle in Giardia has G1, S, G2 and M phases similar to other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…By mining the Giardia genome database for cyclin homologs (Reiner et al, 2008), several genes have been identified as candidates for a mitotic cyclin on the basis of sequence similarity. Each cell contains two diploid nuclei that are replicated concurrently (Bernander et al, 2001;Sagolla et al, 2006), and then simultaneously segregated to opposite poles of the cell by two separate spindles, prior to cytokinesis (Nohýnkova et al, 2000;Sagolla et al, 2006). Thus, the cell cycle in Giardia has G1, S, G2 and M phases similar to other eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Each nucleus has at least one copy of each chromosome (Yu et al, 2002) and the two nuclei have approximately equal quantities of DNA. Therefore, since trophozoites have an estimated ploidy of four (Bernander et al, 2001), it is likely that each nucleus has a ploidy of approximately two. However, the exact number of copies of each chromosome in each nucleus may vary somewhat, as suggested by a cytogenetic evaluation in which the number of chromosomes per nucleus varied between nine and 11 (Tumova et al, 2006), leaving open the possibility of a small degree of aneuploidy.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, these must first fuse and form tetraploid diplokaryons (Bernander et al, 2001;Lee et al, 2014) to trigger meiosis and create genetic diversity? This hypothesis is supported by evidence of diploidy in mononucleate species (Katinka et al, 2001;Cuomo et al, 2012;Selman et al, 2013;Desjardins et al, 2015;Watson et al, 2015) and tetraploidy in Nosema spp.…”
Section: What Drives Genome Homogenization In Encephalitozoon?mentioning
confidence: 99%